The Effect of Reward and Punishment on Job Satisfaction with Work Quality as An Intervening Variable at BPJS Ketenagakerjaan In Medan Raya - Erwinda; Isa Indrawan (International Journal of Management, Economic and Accounting, 2024)
BPJS Ketenagakerjaan is organizing work accident insurance programs, death insurance programs, pension insurance programs, old-age insurance programs and job loss insurance programs. BPJS, collects and collects contributions from participants and employers, receives contribution assistance from the government, manages social security funds for the benefit of participants, collects and manages data on social security program participants, provides benefits and finances services in accordance with the provisions of the social security program. The results of this study are as follows: Work quality has a positive and significant effect on job satisfaction with the original sample value of 0.663 and P values 0.000 Punishment has a positive and insignificant effect on job satisfaction with the original sample value of 9.047 and P values 0.295.Punishment had a positive and significant effect on the quality of work with the original sample value of 0.520 and P values of 0.000. Reward had a positive and significant effect on job satisfaction with the original sample of indigo 0.220 and P values 0.004. Reward had a negative and significant effect on the quality of work with the original sample value of 0.439 and P values of 0.000. Punishment had a positive and significant effect on job satisfaction through indirect work quality with the original sample result of 0.345 and P values of 0.000. Reward has a positive and significant effect on job satisfaction through indirect work quality with the original sample value of 0.291 and P values of 0.000.